2022
DOI: 10.2196/38100
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Web-Based Psychosocial Interventions for Adults With Acquired Brain Injury and Their Caregivers: Systematic Review

Abstract: Background More than 135 million people worldwide live with acquired brain injury (ABI) and its many psychosocial sequelae. This growing global burden necessitates scalable rehabilitation services. Despite demonstrated potential to increase the accessibility and scalability of psychosocial supports, digital health interventions are challenging to implement and sustain. The Nonadoption, Abandonment, Scale-Up, Spread, and Sustainability (NASSS) framework can offer developers and researchers a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 85 publications
(207 reference statements)
0
16
0
Order By: Relevance
“…Intervention implementation outside of a research setting was rarely explored. Other reviews focused on the implementation of eHealth interventions for different groups of informal caregivers [ 27 , 46 , 47 ] similarly found that there was a lack of reporting of implementation determinants related to the inner and outer setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention implementation outside of a research setting was rarely explored. Other reviews focused on the implementation of eHealth interventions for different groups of informal caregivers [ 27 , 46 , 47 ] similarly found that there was a lack of reporting of implementation determinants related to the inner and outer setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature identifies several barriers to the implementation of e–mental health interventions in real-world settings [ 28 , 42 - 44 ], few reviews have focused on barriers to and facilitators of implementing eHealth interventions for informal caregivers [ 27 , 45 - 47 ]. To the best of our knowledge, no review has focused specifically on the implementation of e–mental health interventions for informal caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…These were the (1) condition of ABI, (2) technology used to deliver the interventions in the Social Brain Toolkit, (3) supply- and demand-side value propositions of the Social Brain Toolkit, and (4) adopters of the Social Brain Toolkit. Qualitative survey and interview data pertaining to these 4 domains were anonymously and visually presented via a screen-shared slideshow summary, in combination with preliminary systematic review findings [ 41 ], followed by 1 to 3 prompt questions for group discussion. Plain English questions are available in the study protocol, with a detailed outline of time allocations and procedures provided in supplementary materials [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been recommended that researchers consult stakeholders to identify implementation barriers and tailored strategies [ 37 ]. Therefore, this study aimed to coproduce this implementation knowledge with stakeholders [ 10 ] to support the deployment of implementation strategies: (1) at intervention launch, (2) iteratively during initial pilot (convers-ABI-lity) and 12-month implementation-effectiveness hybrid studies (interact-ABI-lity and social-ABI-lity) [ 41 ], and (3) in future versions. The Australian development team includes speech-language pathologist researchers LT, RR, and MB from the University of Sydney and EP and MM from the University of Technology Sydney, with advisory and steering committees comprising people with living experience of ABI and clinicians supporting them.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies will need to better define the challenging behaviours targeted by the intervention, all the while better identifying the triggers that may be technologically monitored in the most beneficial way for users. This gap could be addressed by involving users in the ongoing development [82][83][84] This review identified the lack of exploitation of available technologies to address the management of challenging behaviours (e.g., artificial intelligence, smart technologies). Future studies may draw on commercialised technologies or existing research in other populations to gather additional ideas on the technologies that could be used and/or adapted for use with the ABI population.…”
Section: Strengths Limitations and Future Perspectivesmentioning
confidence: 99%